Recovery Workers, Latinx Foodways, and Small-Business Development in New Orleans - Fouts, Sarah (FoodAnthropology, 2017)
Within the current context of post-disaster response comes the prolonged challenge of recovery and rebuilding. As families return to devastated homes and businesses after Hurricanes Harvey, Irma and Maria, multiple links passed around on social media recommend where (and where not) to donate funds. Headlines ask who will rebuild each region and warn against the exploitation of past recovery workers. Photos of Beyonce feeding lines of Hurricane victims offer a scintilla of silver lining in a world of increasing human-exacerbated disasters. Little attention, though, is given to the question of how the reconstruction workers that arrive to these devastated regions to help rebuild will sustain themselves—quite literally, who will feed them.